2010
DOI: 10.1186/1750-1326-5-40
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of the Alzheimer's amyloid precursor protein from the endosome to the TGN is S655 phosphorylation state-dependent and retromer-mediated

Abstract: BackgroundRetrograde transport of several transmembrane proteins from endosomes to the trans-Golgi network (TGN) occurs via Rab 5-containing endosomes, mediated by clathrin and the recently characterized retromer complex. This complex and one of its putative sorting receptor components, SorLA, were reported to be associated to late onset Alzheimer's disease (AD). The pathogenesis of this neurodegenerative disorder is still elusive, although accumulation of amyloidogenic Abeta is a hallmark. This peptide is gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(123 citation statements)
references
References 90 publications
(153 reference statements)
3
118
0
Order By: Relevance
“…In addition, it has been proposed that retromer deficiency affects APP processing, thereby increasing A␤ levels (Small et al, 2005;Muhammad et al, 2008). Co-IP studies have indicated that retromer and APP exist in a multiprotein complex, although a direct interaction between APP and any of the retromer components has not yet been identified (Vieira et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been proposed that retromer deficiency affects APP processing, thereby increasing A␤ levels (Small et al, 2005;Muhammad et al, 2008). Co-IP studies have indicated that retromer and APP exist in a multiprotein complex, although a direct interaction between APP and any of the retromer components has not yet been identified (Vieira et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies reported that retromer deficiency in mice and flies increases the production of A␤ (Muhammad et al, 2008), likely by impact on APP sorting (Vieira et al, 2010). Because the retromer complex does not interact directly with APP, we speculated that sorLA is the molecular link between retromer function and APP processing.…”
Section: Introductionmentioning
confidence: 89%
“…At 4 days post-transfection, the cells were divided into 6-well plates coated with 100 g/ml polyornithine and allowed to recover for 5 h. The cells were subsequently treated with 50 g/ml cycloheximide (CHX) in serum-free and antibiotic-free DMEM (29). At the indicated time points, the cells were washed in ice-cold PBS and then harvested in radioimmune precipitation assay buffer as described (14).…”
Section: Methodsmentioning
confidence: 99%
“…To measure human Aβ 40 , we used a commercial ELISA kit consisting of a plate pre-coated with monoclonal anti-Aβ 1A10 (capture antibody), recognizing Aβ [35][36][37][38][39][40] . An HRP-conjugated monoclonal against Aβ [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] was then applied, allowing detection of all N-terminal cleaved Aβ x -40 variants (IBL International).…”
Section: Sandwich Elisa For Aβ Peptide Quantitationmentioning
confidence: 99%